Tuning Ag/Co Metal Ion Composition to Control In Situ Nanoparticle Formation, Photochemical Behavior, and Magnetic-Dielectric Properties of UV-Cured Epoxy Diacrylate Nanocomposites - Batibay, Gonul S.; Yuksel, Sureyya Aydin; Aydin, Meral; Arsu, Nergis (MDPI, 2026)
In this study, we report a reproducible in situ photochemical method for the simultaneous synthesis of metallic and hybrid metal/metal oxide nanoparticles (NPs) within a UV-curable polymer matrix. A series of epoxy diacrylate-based formulations (BEA) was prepared, consisting of Epoxy diacrylate, Di(Ethylene glycol)ethyl ether acrylate (DEGEEA), and Phenylbis (2,4,6-trimethylbenzoyl) phosphine oxide (BAPO), which served as a Type I photoinitiator. These formulations were designed to enable the simultaneous photopolymerization and photoreduction of metal precursors at various Ag+/Co2+ ratios, resulting in nanocomposites containing in situ-formed Ag NPs, cobalt oxide NPs, and hybrid Ag-Co3O4 nanostructures. The photochemical, magnetic, and dielectric properties of the resulting nanocomposites were evaluated in comparison with those of the pure polymer using UV-Vis and Fourier Transform Infrared Spectroscopy (FT-IR), Photo-Differential Scanning Calorimetry (Photo-DSC), Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD), Impedance Analysis, and Vibrating Sample Magnetometry (VSM). Photo-DSC studies revealed that the highest conversion values were obtained for the BEA-Ag1Co1, BEA-Co, and BEA-Ag1Co2 samples, demonstrating that the presence of Co3O4 NPs enhances polymerization efficiency because of cobalt species participating in redox-assisted radical generation under UV irradiation, increasing the number of initiating radicals and leading to faster curing and higher final conversion. On the other hand, the Ag NPs, due to the SPR band formation at around 400 nm, compete with photoinitiator absorbance and result in a gradual decrease in conversion values. Crystal structures of the NPs were confirmed by XRD analyses. The dielectric and magnetic characteristics of the nanocomposites suggest potential applicability in energy-storage systems, electromagnetic interference mitigation, radar-absorbing materials, and related multifunctional electronic applications.
Keywords: photopolymerization; in situ nanoparticle synthesis; hybrid Ag/Co3O4 nanoparticles; photocuring kinetics; dielectric properties; POLYMERIZATION; ABSORPTION; PERMITTIVITY; CONDUCTIVITY; Chemistry; Science & Technology - Other Topics; Materials Science; Physics